Salvage therapy for multiple myeloma with thalidomide and CED chemotherapy - Möhler, Thomas; Neben, Kai; Benner, Axel; Egerer, Gerlinde; Krasniqi, Fatime; Ho, Anthony Dick; Goldschmidt, Hartmut (Blood, 2001)
The feasibility and efficacy of a combination of thalidomide, cyclophosphamide, etoposide, and dexamethasone were studied in 56 patients with poor-prognosis multiple myeloma. Of 50 patients evaluable for response, 4% achieved complete response (CR), 64% partial response (PR), 18% minimal response (MR), 6% stable disease (SD), and 8% progressive disease (PD), resulting in an objective response rate (≥ MR) of 86.0% (76.7% overall objective response rate in intent-to-treat analysis; n = 56). Subsequent to successful remission induction, 18 patients received autologous or allogeneic stem cell transplantation. The median progression-free survival in all patients was 16 months. The median overall survival time could not be calculated, since the last observed death occurred after 16 months of follow-up (median follow-up of 14 months) with a corresponding estimated survival probability of 55%. Severe adverse effects (World Health Organization III/IV) included infectious complications (35.7%) and cardiovascular events (7.1%). The data suggest that Thal improves antitumor activity of salvage chemotherapy regimens in poor-prognosis multiple myeloma.